Sedimentary dynamics in southern Mariana Trench and its controlling factors in past 440 kyr - Shen, Zhongshan; Wang, Haifeng; Chen, Yanping; Cai, Yun; Yi, Liang (Frontiers in Marine Science, 2024)
Understanding sediment dynamics and their controlling factors is essential for Quaternary studies, yet they remain poorly documented in the Mariana Trench. In this work, we examine this basic character from a sediment core collected at a depth of 6470 m from the southern part of the Mariana Trench, documenting changes in sedimentary dynamics over the past ~440 kyr. Our primary findings are as follows: (1) The median grain size is 13.6 ± 12.0 μm, and minimal changes in clay (30.9 ± 9.4%) and silt (56.6 ± 4.0%) contents, indicating a low-dynamic depositional environment; (2) Three grain-size components were identified, characterized by modal changes of ~4/60 μm, ~20 μm, and >100 μm. By comparing these results with various environmental proxies, including glacial-interglacial alternations, eolian input, and bottom-water intensity, we suggest that marine productivity has a dominant influence on deep-sea sediment dynamics, though post-depositional processes also contribute. Additionally, topographical conditions and sea-water chemistry appear to be related to the presence of coarse particles, possibly through coarse transport and micro-nodule development. Overall, grain-size parameters provide a valuable investigative tool for understanding the various influences on sediment dynamics in this region.